Mathematical modeling and determination of thermodynamic properties of jabuticaba peel during the drying process - Costa, Cristian F. (2016)
Jabuticaba is a fruit native of Brazil and, besides containing many nutritional qualities, it also has a good field for use in products such as flour for cakes and biscuits, juice, liqueur, jelly and others. This study aimed to model the drying kinetics and determine the thermodynamic properties of jabuticaba peel at different drying air temperatures. Ripe fruits of jabuticaba (Myrciaria jaboticaba) were collected and pulped manually. Drying was carried out in a forced-air circulation oven with a flow of 5.6 m s -1 at temperatures of 40, 50, 60 and 70 °C. Six mathematical models commonly used to represent the drying process of agricultural products were fitted to the experimental data. The Arrhenius model was used to represent the drying constant as a function of temperature. The Midilli model showed the best fit to the experimental data of drying. The drying constant increased with the increment in drying temperature and promoted an activation energy of 37.29 kJ mol^ -1 . Enthalpy and Gibbs free energy decreased with the increase in drying temperature, while entropy decreased and was negative.